A novel c.916C>A EDA gene pathogenic variant in a boy with X‐linked hypohidrotic ectodermal dysplasia. (1st April 2021) - Mintoff, D.; Pace, N. P.; Mercieca, V.; Bauer, P.; Borg, I.
Abstract: Click here for the corresponding questions to this CME article.